Synthesis of SMT022357 enantiomers and in vivo evaluation in a Duchenne muscular dystrophy mouse model. Issue 2 (10th January 2020) - Babbs, Arran; Berg, Adam; Chatzopoulou, Maria; Davies, Kay E.; Davies, Stephen G.; Edwards, Benjamin; Elsey, David J.; Emer, Enrico; Figuccia, Aude L.A.; Fletcher, Ai M.; Guiraud, Simon; Harriman, Shawn; et al.
Abstract: Following on from ezutromid, the first-in-class benzoxazole utrophin modulator that progressed to Phase 2 clinical trials for the treatment of Duchenne muscular dystrophy, a new chemotype was designed to optimise its physicochemical and ADME profile. Herein we report the synthesis of SMT022357, a second generation utrophin modulator preclinical candidate, and an asymmetric synthesis of its constituent enantiomers. The pharmacological properties of both enantiomers were evaluated in vitro and in vivo . No significant difference in the activity or efficacy was observed between the two enantiomers; activity was found to be comparable to the racemic mixture. Graphical abstract: Image 1 Highlights: A stereoselective synthesis was devised to access enantiomers of phosphinate SMT022357. SMT022357 enantiomers have an improved ADME profile compared to ezutromid. SMT022357 enantiomers show comparable activity and improve the dystrophic phenotype in mdx mice.